All Days 2009
DOI: 10.2118/122574-ms
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between Induced Hydraulic Fracture and Pre-Existing Natural Fracture in a Poro-elastic Environment: Effect of Pore Pressure Change and the Orientation of Natural Fracture

Abstract: This paper investigates the effect of pore pressure change on the interaction of induced hydraulic fracture and natural fracture and the effect of natural fracture orientation. Warpiniski and Teufel's interaction criteria were adopted to evaluate the fracture propagation that would occur after an induced fracture intersects an existing natural fracture. A fully coupled finite element based model is used to simulate hydraulic fracture propagation in a poroelastic formation with existing natura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…For naturally fractured formations under reservoir conditions, natural fractures are narrow apertures which are around 10 -5 to 10 -3 m wide and have high length/width ratios (>1000:1) [1].Typically natural fractures are partially or completely sealed but this does not mean that they can be ignored while designing well completion processes since they act as planes of weakness reactivated during hydraulic fracturing treatments that improves the efficiency of stimulation [2]. The problem of hydraulic and natural fracture interaction has been widely investigated both experimentally [3,4,5,6,7,8] and numerically [9,10,11,12,13,14,15,16,17,18]. Many field experiments also demonstrated that a propagating hydraulic fracture encountering natural fractures may lead to arrest of fracture propagation, fluid flow into natural fracture, creation of multiple fractures and fracture offsets [19,20,21,22] which will result in a reduced fracture width.…”
Section: Introductionmentioning
confidence: 99%
“…For naturally fractured formations under reservoir conditions, natural fractures are narrow apertures which are around 10 -5 to 10 -3 m wide and have high length/width ratios (>1000:1) [1].Typically natural fractures are partially or completely sealed but this does not mean that they can be ignored while designing well completion processes since they act as planes of weakness reactivated during hydraulic fracturing treatments that improves the efficiency of stimulation [2]. The problem of hydraulic and natural fracture interaction has been widely investigated both experimentally [3,4,5,6,7,8] and numerically [9,10,11,12,13,14,15,16,17,18]. Many field experiments also demonstrated that a propagating hydraulic fracture encountering natural fractures may lead to arrest of fracture propagation, fluid flow into natural fracture, creation of multiple fractures and fracture offsets [19,20,21,22] which will result in a reduced fracture width.…”
Section: Introductionmentioning
confidence: 99%
“…(3) Constitutive equation (Rahman et al, 2009) The stress and strain of elastic material are linearly related:…”
Section: Deformation Field Equationmentioning
confidence: 99%
“…In recent years, many researchers began to study the effects of natural fractures on hydraulic fracture propagation using the numerical simulation method, [9][10][11][12][13] and proposed mathematical models to simulate the fracture network propagation. Based on a discrete element numerical simulation and experimental test, Fatahi et al 14 considered that under the condition of a high approach angle, a hydraulic fracture easily passes through a natural fracture,in addition, the filling material in the fracture has a significant effect on the fracture propagation behavior.…”
Section: Introductionmentioning
confidence: 99%